2014
DOI: 10.1001/jama.2014.15063
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sickle Cell Trait With Chronic Kidney Disease and Albuminuria in African Americans

Abstract: IMPORTANCE The association between sickle cell trait (SCT) and chronic kidney disease (CKD) is uncertain. OBJECTIVE To describe the relationship between SCT and CKD and albuminuria in self-identified African Americans. DESIGN, SETTING, AND PARTICIPANTS Using 5 large, prospective, US population-based studies (the Atherosclerosis Risk in Communities Study [ARIC, 1987–2013; n = 3402], Jackson Heart Study [JHS, 2000–2012; n = 2105], Coronary Artery Risk Development in Young Adults [CARDIA, 1985–2006; n = 848],… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
199
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 177 publications
(213 citation statements)
references
References 31 publications
14
199
0
Order By: Relevance
“…In addition, this relationship was independent of baseline eGFR, which is strongly associated with SCT and has been demonstrated to influence D-dimer measurements. 19,20 Although elevated D-dimer levels have long been observed in SCD, the relationship between SCT and D-dimer levels has not been clearly established. Two small case-control studies have shown an association of SCT to D-dimer, but these analyses were limited by sample size and lack of adjustment for confounders.…”
mentioning
confidence: 99%
“…In addition, this relationship was independent of baseline eGFR, which is strongly associated with SCT and has been demonstrated to influence D-dimer measurements. 19,20 Although elevated D-dimer levels have long been observed in SCD, the relationship between SCT and D-dimer levels has not been clearly established. Two small case-control studies have shown an association of SCT to D-dimer, but these analyses were limited by sample size and lack of adjustment for confounders.…”
mentioning
confidence: 99%
“…Our finding that SCT carriers do not have an increased risk of developing hypertension over the course of 25 years aligns with recent findings by Naik et al, who reported that SCT is associated with an increased risk for incident chronic kidney disease, decline in kidney function over time, and albuminuria in their study of almost 16 000 African American participants from various cardiovascular cohorts, including a subset of CARDIA participants. 16 The authors, however, did not find baseline differences in hypertension by SCT status or that the association between SCT and chronic kidney disease was modified by hypertension. In our analysis, we focused on the relationship of SCT status to hypertension, but not chronic kidney disease, as hypertension is better tied to fitness as a predictor of cardiovascular disease risk.…”
Section: Discussionmentioning
confidence: 93%
“…We performed single-gene, single-nucleotide polymorphism (SNP) genotyping by functionally tested TaqMan SNP Genotyping Assays in accordance with manufacturer protocols (Life Technologies, Grand Island, NY). Details about assay design and experimental procedures are described in Naik et al 16 We obtained genotype data for SNP rs334 encoding for hemoglobin S trait, otherwise known as SCT, and for SNP rs33930165 encoding for hemoglobin C trait, another common hemoglobin variant. We genotyped for hemoglobin C trait, given the possibility of coinheritance of hemoglobin S and C in some individuals, which results in a clinically significant variant of sickle cell disease.…”
Section: Genotypingmentioning
confidence: 99%
“…These include proteinuria and/or haematuria, impaired renal function (defined as GFR <80 mL/min/1.73 m2), markedly abnormal urologic and renal vascular abnormalities, any chronic, active viral infection (human T-lymphotropic virus [HTLV], HBV and HCV), history of malignancy, chronic illness, particularly pulmonary, liver, autoimmune, neurologic, or cardiac disease, clinically significant hypertension, nephrocalcinosis, bilateral kidney stones, or recurrent nephrolithiasis, active substance abuse, pregnancy and disorders requiring anticoagulation [35]. The following are some relative contraindications to living kidney donation.…”
Section: Contraindications Of Live Donationmentioning
confidence: 99%